P191 Beta-2 adrenoceptor genotype and response to propranolol in patients with persistent asthma. (14th November 2013) - Anderson, WJ; Short, PM; Lipworth, JLR; Manoharan, A; Palmer, CNA; Lipworth, BJ
Abstract : Background: The arginine-16-glycine (Arg16Gly) beta-2 adrenoceptor (ADR) polymorphism is associated with worse outcomes in patients exposed to regular beta-agonists. We therefore wished to know if Arg16Gly conferred a similar effect in response to beta-antagonists in asthma. Methods and observations: We have performed a retrospective composite analysis of two randomised controlled trials looking at effects of Arg16Gly on the chronic response to propranolol in n = 25 mild to moderate corticosteroid treated persistent asthmatics. We evaluated chronic dosing effects of propranolol given for at least 4 weeks (80mg dose at least 2 weeks) on pulmonary function (FEV1, FEF25–75, total airway resistance at 5Hz: R5) and on salbutamol FEV1 recovery post histamine challenge. Comparisons were made between genotypes comprising one or two copies of Arg (i.e. ArgArg or ArgGly n = 15, FEV1 = 91.1%, FEF25–75 = 58.3%) vs. no copies of Arg (i.e. GlyGly n = 10, FEV1 = 94.1% FEF25–75 = 60.0%). Results: Data are shown in table as change from baseline (i.e. pre vs. post propranolol as means and SEM) within each genotype. Within the Arg genotype there were significant effects of propranolol on FEV1, FEF25–75 and R5 as well as significant blunting of salbutamol response, while in the Gly genotype only salbutamol response was significant. However when comparing the Arg vs. Gly genotypes there were no significant differences for any of the outcomes. Conclusion: Propranolol produces significant effects on pulmonary function and salbutamol response in the Arg genotype, although there were no significant differences between Arg and Gly genotypes.